Signaling private information via accounting system design - Dordzhieva, Aysa; Laux, Volker; Zheng, Ronghuo (Journal of Accounting and Economics, 2022)
Firms that wish to raise capital from external investors can signal favorable private information about their long-term prospects by publicly adopting a liberal accounting system that increases the probability of an overstated financial report. All else equal, the liberal bias deteriorates investors' ability to make efficient investment decisions, which increases the firm's cost of raising capital as investors price protect. But the fact that the firm is willing to adopt such a bias signals booming long-term prospects, which ultimately allows the firm to raise capital at more favorable terms. We also study the effects of accounting standards that require firms to generate unbiased financial reports. Unbiased reporting leads to efficient investment decisions but prevents firms from signaling private information, which reduces their incentive to improve long-term prospects. We find that giving firms discretion over reporting choices is optimal in innovative industries, whereas enforcing unbiased reporting is optimal in traditional industries.